Influence of woody cover and other landscape characteristics on Northern raccoon (Procyon lotor) occupancy - Durbin, Caleb Joseph (My University, 2024)
Northern raccoons (Procyon lotor; hereafter raccoon) are generalist omnivores prevalent across North America. Raccoons occur in a variety of landscapes, especially those including woody areas. Increases in woody cover over the last century may have benefited northern raccoons. My first objective was to evaluate the influence of woody cover and other landscape drivers influencing raccoon occupancy in the contiguous United States. My second objective was to evaluate raccoon occupancy on a smaller scale within Kansas where grasslands are being lost to woody encroachment. To assess continental-scale patterns, I used camera trap data from Snapshot USA from 2019–2021. I analyzed data from 4,512 camera trap survey points and linked raccoon occupancy to land cover variables derived from the 2021 National Land Cover Database (NLCD; Dewitz 2023), 2023 National Hydrography Database (NHD; USGS 2023), and 2022 Rangeland Analysis Platform (RAP; Jones et al. 2018) tree layer. Occupancy models revealed interactions between the proportion of woody cover and the proportion of cropland land use within 1 km was most parsimonious. This effect of woody cover was positively influenced by the proportion of cropland. Occupancy was greatest when there was a proportion of woody cover at 0.10 and a proportion of cropland at 0.90 (βwoody = 0.632, SE = 0.119; βcrop = 4.121, SE = 0.715; βwoody:crop = 1.905, SE = 0.359). Additionally, raccoon occupancy is greater in areas closer to water (β = -0.722, SE = 0.0773). My results indicate woody cover may increase raccoon use, particularly in landscapes with cropland. Raccoons provide many positive and negative impacts to ecosystems and may benefit from altered cropland landscapes that provide minimal woody cover. Building on these findings, I aimed to find if similar patterns of raccoon occupancy are observed in woody encroached areas specifically within Kansas. The invasion of woody species is a major threat to grasslands and grazing operations. Woody species invasion not only poses challenges for grasslands and grazing operations but also contributes to a widespread decline in grassland bird species. The presence of woody plants may benefit nest predators like raccoons. My objective was to relate woody cover to raccoon occupancy in landscapes that can provide inference on how woody encroachment could alter raccoon distributions. I used camera traps and remotely sensed data to evaluate the influence of landscape composition on raccoon occupancy in Kansas. I conducted a stacked single-season occupancy analysis to identify relationships with site covariates. My most-supported single-season occupancy model included the additive influence of proportion of grassland within 1 km and distance to water and suggested that occupancy probabilities were lower at survey points with greater proportions of grassland and farther from water sources (βintercept = -1.89, SE = 0.25, βgrass = -1.072, SE = 0.22, βdistwater = -0.58, SE = 0.24; Fig. 2). Another competitive model included proportion of cropland within 1 km and proportion of woody cover within 1 km in an additive model and suggested that raccoon occupancy increased with woody cover and cropland (βintercept = -1.81, SE = 0.24, βcrop= 1.13, SE = 0.22, βwoody = 0.63, SE = 0.20). My results suggested a positive influence of woody cover, proximity to water, croplands, and a negative influence of grassland on raccoon occupancy. Consequently, raccoons may derive benefits from woody encroachment in Kansas. Conserving grassland areas may decrease raccoon occupancy and in doing so may reduce the use of areas that are important for landowners and other species and may then ease the human-wildlife conflicts that exist for this species with the potential for disease spread and damage to crops as well as benefit ground nesting birds.
Keywords: Northern raccoon; Occupancy; Woody encroachment; Habitat use